Population Density: An Underlying Mechanism Between Road Transportation and Environmental Quality - Din, Ashraf Ud; Ming, Jian; Vega-Muñoz, Alejandro; Salazar Sepúlveda, Guido; Contreras-Barraza, Nicolás (Frontiers in Environmental Science, 2022)
Mounting degradation in the environmental quality (EQL), specifically from the transport industry, is a big threat and challenge for sustainable development. The transport sector’s emission has gained researchers’ attention on climate change and transportation because of its increasing share in global emission. This study, thus, aims to analyze the links among road infrastructure (RIN), road transport energy consumption (RTEC), and environmental quality with the moderating role of population density (PDN). The study has used a dataset of five South Asian countries from 1971 to 2014. The study applies the Breusch–Pagan LM test to identify the issue of cross-sectional dependence. CIPS (second-generation unit root test) is applied to check the stationarity properties of the data, whereas the Westerlund (Oxf. Bul. Econ. Stat., 2007, 69 (6), 709–748) co-integration test is used to confirm the long-run association among the variables. Moreover, a fully modified ordinary least square (FMOLS) model is applied to analyze the effect that road transportation has on environmental quality. The study finds a positive effect of road infrastructure, road density (RDN), energy intensity (EIN), and road transport energy consumption on transport-generated emissions, which indicates that road transportation is harmful to environmental quality. Our results confirm the significant moderating role of population density in strengthening the relations of road infrastructure, road transport energy consumption, and environmental quality. It is concluded that population density works as a bridge between road infrastructure, road transport energy consumption, and environmental quality, which helps capture a strong impact of road transportation. We offer the planners of road transportation with a novel and practical approach to examine population density changes policy in the growing countries to analyze the environmental quality.